[Another chance for peace ; Light in the darkness ; Kilabot ng mga Kolehiyala [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Deals with President Ramos scrapping the anti-conversion law and starting a new round of peace talks with the rebels, both left and right. Mindanao overcomes the longest power interruptions through the Voluntary Load Curtailment Program. Interview with Hajji Alejandro and Ariel Rivera about their concerts, Kilabot.
Another chance for peace (16 min.) -- Light in the darkness (12 min.) -- Kilabot ng mga Kolehiyala (16 min.)
VHS.
Keywords: Alejandro, Hajji -- Interviews; Rivera, Ariel -- Interviews; Voluntary Load Shedding Program; New People's Army; Peace negotiations -- Philippines; Electric power failure -- Philippines -- Mindanao